Quality of COVID-19 notification data in pregnant women: a descriptive study (Brazilian Journal of Health Research, 2023)
Introduction:The adequate and systematic monitoring of COVID-19 cases occurs through the use of a qualified information system. The notification of COVID-19 cases in Espírito Santo took place through its own health information system established in January 2020, the e-SUS Health Surveillance (e-SUS VS), through which it was possible to monitor the most reported cases. Quickly as well as risk groups, such as pregnant women who have shown high incidence and maternal mortality from this disease. Objective: To describe the quality and timeliness of COVID-19 notification data in pregnant women, obtained through the new e-SUS VS information system implemented in Espírito Santo. Methods: Descriptive study using data obtained through e-SUS VS. Completeness in completing the notification was classified as excellent (less than 5% incomplete), good (5% to 10%), fair (10% to 20%), poor (20% to 50%) or very poor (50% or more). Opportunity was defined by the difference between the dates of symptom onset and notification. Results: 8,989 notifications were identified in pregnant women. The e-SUS VS notification for COVID-19 has 59 variables, the completeness of 53 (89.83%) variables was excellent, good and regular in 1 (1.70%), and poor in 4 (6.77%). The opportunity had an average of 3.37 days. Conclusion: The quality of the e-SUS VS data was excellent, making it an important source of information to support actions and the improvement of public policies aimed at this risk group.
Keywords: COVID-19; Pregnancy; Health information systems; Disease notification; Epidemiology descriptive